Education, Lack of Complementary Investment and Underemployment In an Open Economy - Sugata Marjit; Rashmi Ahuja; Abhilasha Pandey (Center for Economic Studies and ifo Institute (CESifo), 2021)
In many developing economies rate of unemployment is increasing with skill accumulation and thereby leading to underemployment. Our paper offers to look at skill formation as a demand side problem not as a traditional supply side problem and also how skill formation or education affects unemployment among the remaining uneducated. We have developed a general equilibrium model of a small open developing economy incorporating skill formation, unemployment of unskilled labour in the formal sector and an informal sector which absorbs unemployed workers at a flexible wage rate. In this set up greater education for a group may generate educated unemployment within the group and increase unemployment of the uneducated outside the group leading to underemployment through the expansion of the informal sector. Both effects are due to shortage of complementary investment in production activities. Our theoretical findings are motivated by existing empirical evidence and a fresh empirical exercise undertaken using panel data of 32 countries.
Keywords: J24; J31; E26; E24; 330; skill formation; informal employment; skilled-unskilled wage inequality; underemployment